Digital transformation of SMEs: Leveraging social media to market mangrove-based products - Tika Dwi Ariyanti; Innas Rovino Katuruni; Rahma Nur Praptiwi; Sri Isti Untari; Nur Hasyim; Kristin Lukitaningrum; Maria Nino Istia; Anita Rahmawati; M. Jamal Al Bakri (Universitas Muhammadiyah Magelang, 2024)
This community service activity aimed to enhance the sales of mangrove-based products produced by the Tanjung Jalakarya SMEs group through the utilization of social media. Prior to the program, the group faced challenges in promoting and selling their products. Through the community service program, the team provided equipment, training on labeling and packaging, and mentorship on social media usage. As a result, within six months, there was a 30% increase in sales. This demonstrates the effectiveness of empowering SMEs groups with knowledge and skills in utilizing social media to expand their market reach and increase their income.